2021
DOI: 10.54991/jop.2020.28
|View full text |Cite
|
Sign up to set email alerts
|

Response between tree-rings of Pinus kesiya and daily climate data – A study from Manipur, Northeast India

Abstract: A 39 years (1980–2018 C.E.) long tree–ring width chronology of Khasi Pine (Pinus kesiya) was developed using 36 tree cores collected from Manipur, Northeast India. The significant dendrochronological potential of this tree was achieved from this region, based on tree–ring chronology statistics. A linear response between ring–width chronology of P. kesiya and daily gridded climate (mean temperature and rainfall) records has been established. A significant negative association has been observed between daily mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…The time window considered for BCFs and MCFs spans from August of the year preceding growth-ring formation (n−1) to current August (n). In addition, to retrieve more detailed information on anatomical and radial growth responses to climatic parameters ( Jevšenak and Levanič, 2018 ; Thomte et al., 2020 ), we computed MCFs between RW and those vessel-related trait series that were identified from the PCA (i.e. CNO and MLA25, see below) and daily temperature and precipitation series from the Segl-Maria weather station averaged over time periods ranging from 10 to 150 days data using the dendroTools R package ( Jevšenak and Levanič, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…The time window considered for BCFs and MCFs spans from August of the year preceding growth-ring formation (n−1) to current August (n). In addition, to retrieve more detailed information on anatomical and radial growth responses to climatic parameters ( Jevšenak and Levanič, 2018 ; Thomte et al., 2020 ), we computed MCFs between RW and those vessel-related trait series that were identified from the PCA (i.e. CNO and MLA25, see below) and daily temperature and precipitation series from the Segl-Maria weather station averaged over time periods ranging from 10 to 150 days data using the dendroTools R package ( Jevšenak and Levanič, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…The restriction of climate variables to calendar months may dilute the climate signal embedded in tree rings since months are arbitrary limits and do not correspond with tree physiological processes. Recent improvements in methodology and availability of high-resolution daily climate records have aided in the analysis of tree growth-climate response to daily climate (Beck et al, 2013;Pritzkow et al, 2016;Jevšenak & Levanič, 2018;Nechita et al, 2019;Thomte et al, 2021;Magnússon et al, 2023). Studies using daily climate have demonstrated an enhanced relationship between climate and tree growth indices (Sun & Liu, 2016;Jevšenak, 2019;Thomte et al, 2022) and the potential for capturing the influence of short, extreme climate events on the growth of trees (O'Donnell et al, 2021;Trumper et al, 2022).…”
Section: Introductionmentioning
confidence: 99%